The Role of Strategic Management in Determining Business Success in the Era of Digital Disruption - Anggella Chandini; Finola Fiftem Eka Putri; , Mardifa Wahyu Putri; Jefri Andriadi; M. Hafidz Aima (Journal of Innovative and Creativity, 2025)
The era of digital disruption has presented significant challenges for organizations across various sectors to remain competitive in a rapidly changing business environment. Exponential technological change, shifting consumption patterns, and increasing market complexity require organizations to implement strategies that are not only reactive, but also innovative and adaptive. In this context, strategic management plays a central role in determining business direction, competitive advantage, and sustainability. This study aims to examine in depth how strategic management contributes to business success amidst the pressures of digital disruption. This study uses a descriptive qualitative approach using literature studies and interviews with ten business actors from the technology and retail sectors in Indonesia. The results show that long-term planning, the implementation of data-driven strategies, flexibility in decision-making, and an organizational culture that supports innovation are key factors in facing the era of disruption. Strategic managers also act as agents of change, not only guiding the organization structurally but also shaping a digital mindset across all levels of the organization. This research provides practical contributions for business actors in designing more responsive business strategies, while also providing a basis for policymaking at the organizational and government levels to strengthen national business resilience in the digital era.